OUTLAYS ON INVESTMENTS IN FARMS SPECIALIZING IN MILK PRODUCTION, DEPENDING ON THE DEGREE OF PRODUCTION CONCENTRATION - Wysokiński, Marcin; Dziwulski, Mariusz; Jarzębowski, Sebastian (Acta Scientiarum Polonorum. Oeconomia, 2013)
The aim of this study was to determine the level of outlays on investments farms specializing in milk production depending on the scale of dairy cows breeding. The research involves agricultural holdings in Poland covered by FADN system in 2004-2009, in which the value of milk production in the total output was more than 60%. Studies have shown proportional relationship between the size of outlays on investments and the number of cows in the herd. In addition, the relationship was proved between an investment activity of farmers, depending on the situation of the milk market and dairy farm incomes. The article also examines the level of net investment in the studied groups of households per 1 ha of agricultural land, indicating a high diversity of farms in this regard.